A STUDY OF THE VICTIM BLAMING - Khan Umer M. Muhammad; Dr. Rashida Qazi; Adeela Mushtaq; Sajawal Qayyum; Dr. Nida Fatima; Iqra Nazeer (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
On this topic, different researchers/Authors have published various articles to explain the issue of Victim-blaming. Blaming the victim in cases of sexual violence may be a worldwide wonder, but it is especially endemic in patrilineal social orders. Victims of rape are extraordinarily helpless for being faulted for their assault relative to victims of other interpersonal violations and in this way number of research have been conducted to get why this is often the case. It is Qualitative research, every information is explored from the Internet, by going through different research articles and, also by reading different newspaper articles published on this topic. The scope of my research is that accusing victims of any age group or gender for provoking abuse is not acceptable.